(untitled) (Desenvolvimento em Questão, 2025)
In view of the themes discussed on urbanization, research on the processes of urban and city restructuring and the creation of new centralities is recurring. From this perspective, this work presents a reflection on the city of Parauapebas, guided by the new expressions of intra-urban centrality that are reproduced in it, which play a fundamental role in its urban restructuring. In this way, the objective is to understand the economic and spatial dynamics that (re)define the Main Center, materialize the formation of new centralities and constitute new patterns of commerce and services outside the central area. As a methodological basis, theoretical research, fieldwork, photographic records, research on websites and official documents, preparation of maps, among others, were used. Therefore, it is important to understand that the socio-spatial arrangement of Parauapebas follows the historical outline of the appropriation of different agents producing urban space, mainly the State and big capital. The results obtained point to the characterization of the Main Center in the Rio Verde neighborhood, especially due to the city’s formation context, consolidating it as a representative and functional centrality, based on the tertiary sector. Through urban expansion, new centralities are created and constitute dynamics and modifications in the production process within the scope of urban and city restructuring. Thus, Avenida dos Ipês, in the Cidade Jardim neighborhood, stands out as an area for locating new standards and functions of retail commerce.